Predictors of career transition success of second-career novice teachers in Selangor - Md Isa, Najmina; Mohd Rasdi, Roziah (Human Resource Management Academic Research Society, 2015)
The aim of this research was to examine the predictors of career transition success among second-career novice teachers. Specifically, the research examined the importance of the following variables; protean career, self-efficacy, perceived organizational support and organizational socialization. A self-report questionnaire was used to obtain data from a sample of Selangor novice teachers in secondary and primary schools (N = 150). The findings showed that self-efficacy and organizational socialization were significant predictors of career transition success. Theoretical and practical implications of the research were discussed.